State, society, and displaced people in South Asia - Ahmed, Imtiaz, 1958-; Dasgupta, Abhijit; Sinha-Kerkhoff, Kathinka (Dhaka : University Press, 2004)
Contributed articles presented earlier at a seminar on South Asian refugees and their transnational migration.
Includes bibliographical references and index.
The university press
Keywords: Refugees -- South Asia -- Congresses; Transnationalism -- Congresses; South Asians -- Relocation -- Congresses